Lumbosacral transitional vertebrae morphology: a South African population - Paton, Glen James (Department of Human Biology, 2022)
Lumbosacral transitional vertebrae (LSTV) are defined as congenital anatomical variations, observed unilaterally or bilaterally, in which the transverse process of the last lumbar vertebra exhibits signs of dysplasia evident as increased craniocaudal height, with varying degrees of articulation or fusion to the ‘first' sacral vertebra. Such variations give rise to vertebral morphology that may display lumbar or sacral characteristics at the terminal lumbar spine, together with subsequent enumeration variation. The purpose of this study was to establish baseline data on the prevalence rates of LSTV and to describe the morphological characteristics (Type, subtype, frequency of side and spinal enumeration) of LSTV in the South African population. This study was subdivided into two main sections, namely Part 1: medical imaging appraisal and Part 2: osteological morphology appraisal. In Part 1, both retrospective and prospective cohort randomised sampling methods of data collection of medical images were used. The appraisal of the medical images included radiographs, magnetic resonance imagers and computerised tomography scans. Prevalence rates, utilising the Castellvi et al. (1984) classification, were established via radiographs only. Additionally, lumbar spine enumeration, namely lumbarisation and sacralisation, was made through the appraisal of lumbar radiographs. Images were obtained from medical radiology practices located at Groote Schuur Hospital in Cape Town, Western Cape Province and Charlotte Maxeke Johannesburg Academic Hospital in Johannesburg, Gauteng Province. The total imaging cohort included 3096 individuals of which 308 individuals (10%) were found to contain LSTV. Prevalence rates were further evaluated by subdivision of the three largest ancestries in South Africa. Ancestries were classified as African (n=1032), Mixed (n=1032) and European (n=1032). The prevalence of LSTV in the three ancestral groups was 10.5%, 9.3% and 9.9% respectively and the sex distribution was greater in females (52.1%) then in males (47.9%). The morphological assessment found the prevalence of LSTV by Type was Type II (67.9%) followed by Types III (27.6%) and IV (4.5%). The most frequent subtype by prevalence was Type IIA (41.9%) followed by Type IIB (26%), Type IIIB (21.8%), and Type IV (5.8%). Additionally, the frequency of side was bilateral (47.7%), left (26.6%), right (21.1%), and other (4.5%). Comparison of ancestry and spinal enumeration analyses established statistical significance for individuals of African-ancestry (67.0%) and Mixed-ancestry (72.9%) both of which demonstrated a greater affinity of prevalence for sacralisation (p=0.008), with a small effect size (V=0.178) over the European-ancestry subgroup (52.4%). Furthermore, a statistical significance with a medium effect size (V=0.256) was found in males (p=0.010) when comparing ancestry and spinal enumeration between sexes. In Part 2, a systematic search of the total cadaveric skeletal collection housed at the University of Witwatersrand (the Dart Collection of skeletons) yielded 1797 human skeletal specimens of between 21 and 65 years of age at time of death. One-hundred and fourteen skeletal remains were identified as containing LSTV. Damage and loss of vertebral elements resulted in a subset of 91 LSTV for study. A sex balanced control group cohort of 30 males and 30 females was selected at random from the Dart Collection for comparative analyses. A number of osteometric measurements were evaluated comparing the LSTV and control group cohorts. Numerous osteometric comparisons were statistically significant highlighting the many changes in lumbar and sacral morphology associated with LSTV. There are several original findings to emerge. Thisis the first study to establish the prevalence of LSTV in a large sample from the South African population, subdivided into the three largest ancestral groups. Novel findings associated with LSTV include iliolumbar articulation, bipartition of the sacral foramen, intra-articular vacuum phenomenon of accessory articulations of LSTV, enlargement of the contralateral TVP associated with Types III and IV LSTV, lumbar ossified bridging syndrome and a novel complex named by the researcher as the transverso-sacro-iliac articulation. Furthermore, the researcher has proposed three modifications to the Castellvi et al. (1984) classification, namely (1) that there should be a sub-classification of the Type IV LSTV into right and left nomenclature, (2) the inclusion of a new subtype of Type II LSTV morphology, a unilateral right or left iliolumbar articulation associated with contralateral Type IIA morphology, and (3) a modified morphological classification of LSTV based on the presence of an extended sacroiliac articulation either directly or via the transverso-sacro-iliac articulation. The latter effectively increases the size of the sacroiliac joint and is thought to increase spinopelvic stability. The transverso-sacroiliac articulation was demonstrated for all clinically significant LSTV Types (II-IV), both unilateral (right or left) and bilateral. Finally, this is the first study to incorporate an in situ and an ex situ study in the same population by examining spinal morphology of LSTV using medical images and skeletal remains for descriptive analyses.